Brazilian large family firms & non-Family firms: bridging regional context and top management team gender diversity - Franciele Beck; Kyung eun Park; Jéssica Merco do Nascimento e Silva; Tatiane Meurer; Stephan Klaus Bubeck; Melania Riefolo; Jochen Baumgardt; Lech Suwala; Jan-Philipp Ahrens (Review of Regional Research, 2025)
The importance of family businesses in the global economic landscape is widely acknowledged, and initial progress has been made in exploring the interrelationship between family businesses and the contexts in which they operate. This study investigates the influence of family businesses, geographic location, and gender diversity within Brazilian companies. For this purpose, it uses an extensive database, encompassing over 2.8~million active Brazilian companies, and employs the Atalanta algorithm to identify family businesses. Using a~logit model, the results reveal significant differences in gender diversity between family and non-family businesses, as well as variations between urban and rural areas. Theoretical contributions include advances in understanding the importance of the regional context in the management of family businesses, as well as expanding the debate on gender diversity in such business contexts. Practically, family businesses can adopt more inclusive policies to enhance their performance, especially in regions where gender diversity is still limited. Regional public policies that encourage inclusion could also promote the development and long-term sustainability of family businesses. - – – Die Bedeutung von Familienunternehmen im globalen wirtschaftlichen Umfeld ist weithin anerkannt und es wurden erste Fortschritte bei der Erforschung der Wechselwirkungen zwischen Familienunternehmen und den Kontexten, in denen sie tätig sind, erzielt. Diese Studie untersucht den Einfluss von Familienunternehmen, geografischer Lage und Geschlechterdiversität in brasilianischen Unternehmen. Zu diesem Zweck wird eine umfangreiche Datenbank verwendet, die mehr als 2,8 Mio. aktive brasilianische Unternehmen umfasst. Dabei wird der Atalanta-Algorithmus eingesetzt, um Familienunternehmen zu identifizieren. Mithilfe eines Logit-Modells zeigen die Ergebnisse signifikante Unterschiede in der Geschlechterdiversität zwischen Familien- und Nicht-Familienunternehmen sowie Unterschiede zwischen städtischen und ländlichen Räumen. Auf der theoretischen Ebene leistet die Abhandlung einen Beitrag, indem sie sowohl Fortschritte beim Verständnis der Bedeutung des regionalen Umfelds für die Führung von Familienunternehmen erzielt als auch hierzu eine Debatte über Geschlechtervielfalt in Geschäftskontexten integriert. Für die Praxis werden für Familienunternehmen inklusivere Politiken empfohlen, um ihre Performance zu steigern, insbesondere in Regionen, in denen die Geschlechterdiversität noch begrenzt ist. Eine inklusionsfördernde Regionalpolitik könnte ferner eine Entwicklung und langfristige Nachhaltigkeit von Familienunternehmen unterstützen.
Keywords: R1; 910; Large firms; Family firm; TMT gender diversity; Regional environment; Firm age; Brazilian geographical location